Preparation method and application of main grid slurry of high-conductivity silver coated conductive powder
By regulating the compound ratio of organic carrier, inorganic glass powder, silver-coated conductive powder and silver powder in photovoltaic conductive materials, and using silver-coated powder to replace part of the silver powder, the problem of high cost of silver powder in existing conductive materials is solved and cost reduction is achieved. and improve performance.
Patent Information
- Application Number
- CN202411612939.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-01-24
AI Technical Summary
In the photovoltaic industry, bank powder accounts for 85-90% of the existing conductive materials, which is high in cost and is difficult to meet the requirements of reducing costs and improving efficiency.
By adjusting the compound ratio of organic carrier, inorganic glass powder, silver-coated conductive powder and silver powder in the busbar slurry, silver-coated powder with certain conductivity is used to replace part of the silver powder, and the preparation process parameters are combined to reduce costs and improve efficiency. Slurry properties.
While ensuring the electrical performance, the use of silver powder, reducing production costs, and improving the overall performance of the slurry.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of conductive materials and solar cells, and in particular relates to a preparation method and application of a main grid slurry of highly conductive silver-coated conductive powder. Background Art
[0002] The process of converting solar energy into electrical energy in the photovoltaic industry is mainly achieved through photovoltaic cells based on semiconductor materials (such as silicon). The working principle of the whole system is that when photons (energy units in sunlight) shine on photovoltaic cells, they will excite electrons to jump from the valence band to the conduction band, thereby forming a potential difference between electrons and holes, and generating current through an external circuit.
[0003] The photovoltaic industry is developing rapidly, not only in terms of installed capacity, but also in terms of technological updates. Therefore, the supply of photovoltaic main materials has also increased significantly. As a conductive material for photovoltaic cell metallization, 85-90% of it is metallic silver, which is expensive and difficult to meet the requirements of cost reduction and efficiency improvement. Therefore, a new slurry component is needed to replace part of the silver powder, which can reduce costs while ensuring quality. Summary of the invention
[0004] The purpose of the present invention is to solve the above-mentioned problems existing in the prior art, and proposes a preparation method and application of a main grid slurry of a highly conductive silver-coated conductive powder, adjusts the compounding ratio of the organic carrier, inorganic glass powder, silver-coated conductive powder and silver powder in the main grid slurry, uses silver-coated powder with a certain conductivity to replace part of the silver powder, and combines the preparation process parameters to reduce the cost while improving the overall performance of the slurry.
[0005] The technical solution of the present invention is: The present invention provides a method for preparing a main grid slurry of a highly conductive silver-coated conductive powder, comprising the following steps: (1) Mixing part of the organic carrier with inorganic glass powder, wherein the inorganic glass powder accounts for 65-90%, and stirring for 20-40 minutes until there is no obvious granular feeling and the fineness is less than 50 μm, to obtain a first mixture; In step (1), a portion of the organic carrier and the inorganic glass powder are mixed, and the weight ratio of the inorganic glass powder in the mixture is 65-90%. For example, the inorganic glass powder can account for 65%, 67%, 70%, 72%, 75%, 78%, 80%, 83%, 85%, 87% or 90%, etc., but is not limited to the listed values, and other values not listed in the range are also applicable.
[0006] The stirring time is 20 to 40 min, for example, it can be 20 min, 23 min, 25 min, 27 min, 30 min, 32 min, 35 min, 37 min or 40 min, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0007] The above-mentioned fineness is required to be below 50 μm, for example, it can be 50 μm, 48 μm, 46 μm, 45 μm, 43 μm, 40 μm, 35 μm, 30 μm, 25 μm, 20 μm, 15 μm, 10 μm or 5 μm, but is not limited to the listed values, and other unlisted values that meet the requirement of being below 50 μm are also applicable.
[0008] (2) transferring the first mixture to a three-roll mill and rolling it until the fineness is ≤3 μm to obtain a glass slurry; (3) Mix the remaining organic carrier with the glass slurry, the silver-coated conductive powder and the silver powder, and stir for 1 to 2 hours until there is no obvious granularity and the fineness is less than 10 μm, to obtain a second mixture; The stirring time is 1 to 2 h, for example, 1 h, 1.2 h, 1.5 h, 1.7 h or 2 h, but is not limited to the listed values. Other values not listed below 50 μm are also applicable.
[0009] The fineness is below 10 μm, for example, it can be 10 μm, 9 μm, 8 μm, 7 μm, 6 μm or 5 μm, but is not limited to the listed values. Other unlisted values that meet the requirement of being below 10 μm are also applicable.
[0010] (4) The second mixture is transferred to a three-roll mill and rolled until the fineness is ≤3 μm to obtain a main grid slurry.
[0011] The fineness is ≤3 μm, for example, it can be 3 μm, 2 μm or 1 μm, but is not limited to the listed values. Other unlisted values that meet the requirements of being below 3 μm are also applicable.
[0012] The preparation method of the present invention mixes part of the organic carrier and the inorganic glass powder, and rolls them with a three-roll mill to a fineness of ≤3 μm. The two components are first prepared into glass paste. On the one hand, the hardness of the inorganic glass powder is relatively large. After being directly added to the conductive paste, the fineness of the paste is likely to be greater than 3 μm, while the silver-coated conductive powder cannot be dispersed by three rollers by adjusting the gap of the three-roll mill to 5 μm gap or pressure mode. The main reason is that if the gap is too small, the silver roller of the coating layer is easy to fall off, resulting in loss of electrical performance.
[0013] Furthermore, the raw materials for preparing the main grid slurry include, by weight: 8-30 parts of organic carrier, 0.5-5 parts of inorganic glass powder, 0.5-65 parts of silver-coated conductive powder, and 0.5-65 parts of silver powder; The raw material contains 8-30 parts of organic carrier, for example, 8 parts, 10 parts, 12 parts, 15 parts, 18 parts, 20 parts, 23 parts, 25 parts, 27 parts or 30 parts, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0014] The inorganic glass powder is 0.5-5 parts, for example, it can be 0.5 parts, 1 parts, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts, 4 parts, 4.5 parts or 5 parts, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0015] The silver-coated conductive powder is 0.5-65 parts, for example, it can be 0.5 parts, 1 parts, 5 parts, 10 parts, 20 parts, 30 parts, 35 parts, 37 parts, 40 parts, 43 parts, 45 parts, 47 parts, 50 parts, 55 parts, 58 parts, 60 parts or 65 parts, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0016] The amount of silver powder is 0.5-65 parts, for example, it can be 0.5 parts, 1 parts, 5 parts, 10 parts, 12 parts, 15 parts, 17 parts, 20 parts, 23 parts, 25 parts, 27 parts, 30 parts, 32 parts, 35 parts, 40 parts, 50 parts, 60 parts or 65 parts, but is not limited to the listed values, and other values not listed within the range are also applicable.
[0017] The particle size of the inorganic glass powder is 0.5-3 μm; The particle size of the silver-coated conductive powder is 0.2-10 μm, and its shape includes one or more of spherical, quasi-spherical, flake, fibrous, and dendritic; The silver powder has a particle size of 0.2-3 μm and a shape of sphere, quasi-sphere, flake, fiber or dendrite; The organic carrier comprises the following components in parts by weight: 1 to 15 parts of resin, 70 to 90 parts of solvent, and 2 to 15 parts of auxiliary agent.
[0018] Furthermore, the method for preparing the organic carrier comprises the following steps: Weigh each component according to the weight portion in the organic carrier, dissolve the weighed resin and solvent at a temperature of 50-90°C, disperse at a speed of 500-1000 rpm until clear and transparent, cool to room temperature, add an auxiliary agent to mix, and stir for 1-2 hours to obtain an organic carrier.
[0019] The above dissolution temperature is 50-90°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0020] Furthermore, the raw materials for preparing the main grid slurry include, by weight: 20-30 parts of organic carrier; 2.5-4 parts of inorganic glass powder; 35-65 parts of silver-coated conductive powder; Silver powder 0.5-35 parts.
[0021] Furthermore, the inorganic glass powder is a powder obtained by melting inorganic oxides at a high temperature of 900-1500°C to form a glass body, cooling, grinding or jet milling; The inorganic oxides include lead oxide, titanium oxide, copper oxide, silicon dioxide and boron oxide.
[0022] The above melting temperature is 900-1500°C, for example, it can be 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, 1250°C, 1300°C, 1350°C, 1400°C, 1450°C or 1500°C, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0023] Furthermore, the silver-coated conductive powder is one or more of silver-coated copper powder, silver-coated tin powder, silver-coated nickel powder, silver-coated carbon powder, silver-coated tin-coated copper powder, silver-coated carbon-coated copper powder, silver-coated nickel-coated carbon powder, silver-coated tin-coated carbon powder, and alloy powder; The mass percentage of silver in the silver-coated conductive powder is 10-80%, for example, it can be 10%, 20%, 25%, 30%, 40%, 45%, 50%, 55%, 60%, 65%, 70% or 80%, etc., but is not limited to the listed values, and other values not listed within the range are also applicable.
[0024] Furthermore, in the organic carrier, the resin is selected from at least one of ethyl cellulose resin, cellulose resin, PVB resin, SEBS resin, SBS resin, acrylic resin, polyester resin, polyurethane resin, and phenolic resin; The solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol hexyl ether, diethylene glycol butyl ether acetate, diethylene glycol dibutyl ether, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, tributyl citrate, dibutyl phthalate, isooctyl palmitate, terpineol, and DBE; The additives include one or more of dispersants, leveling agents, coupling agents, and thixotropic agents.
[0025] Further, the dispersant includes polyurethane modified dispersant, modified polyester dispersant, oleic acid, stearic acid, TDO, acrylic dispersant; The leveling agent includes silicone, acrylic, polysiloxane, and silicone oil; The coupling agent includes a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a chromium complex coupling agent; The thixotropic agent includes an inorganic thixotropic agent, hydrogenated castor oil and its derivatives, and polyamide wax.
[0026] The present invention also provides the use of a main grid slurry of a highly conductive silver-coated conductive powder prepared by any of the above-mentioned preparation methods in a main grid of a photovoltaic solar cell sheet.
[0027] Beneficial effects of the present invention: The invention provides a new preparation method, wherein an organic carrier, inorganic glass powder, silver-coated conductive powder and silver powder in raw materials are compounded to prepare a conductive paste, wherein the organic carrier improves the printing performance of the conductive paste, so that the conductive paste has a relatively good aspect ratio and a low wet weight, the silver-coated conductive powder and the silver powder give the conductive paste good conductive performance, and the inorganic glass powder, the silver-coated conductive powder and the silver powder are sintered at a high temperature to assist the silver-coated conductive powder and the silver powder to form an Ag-Si alloy layer with the surface of a silicon wafer, thereby ensuring good contact.
[0028] The present invention adjusts the printing properties, conductivity, tension and other properties of the slurry by regulating the compounding ratio of the organic carrier, the inorganic glass powder, the silver-coated conductive powder and the silver powder, thereby enhancing the overall performance of the slurry; and, by using the silver-coated powder with a certain conductivity to replace part of the silver powder, the usage of the silver powder can be greatly reduced, thereby reducing the production cost. DETAILED DESCRIPTION
[0029] To further understand the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0030] A main grid slurry of highly conductive silver-coated conductive powder, comprising the following raw materials in parts by weight: 15 parts of organic carrier 2 parts inorganic glass powder Silver-coated nickel powder (30% silver) 45 parts Aluminum alloy 5 parts 33 parts of silver powder Among them, the raw materials of the organic carrier are: Ethyl cellulose resin 10 parts 20 parts of diethylene glycol butyl ether 48 parts of diethylene glycol butyl ether acetate 10 parts of tributyl citrate Polyamide wax 5 parts TDO 5 parts 2 parts dimethyl silicone oil A method for preparing a main grid slurry of a highly conductive silver-coated conductive powder is as follows: Step 1, ethyl cellulose, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, tributyl citrate, polyamide wax, TDO, and dimethyl silicone oil are prepared according to the above weight parts, and dispersed and dissolved in a high-speed disperser at a temperature of 80°C, a speed of 1000 rpm, and a time of 1 hour until it becomes clear and transparent, and then cooled to room temperature to obtain an organic carrier; Step 2: Take a portion of the organic carrier prepared in step 1, add inorganic glass powder and mix to obtain a mixture, wherein the organic carrier accounts for 33.33% of the two mixed raw materials and the inorganic glass powder accounts for 66.67%. Stir in a contact planetary mixer for half an hour until there is no obvious granularity and the fineness is less than 45 μm, thereby obtaining a first mixture; Step 3: Transfer the first mixture to a three-roll mill and roll it to a fineness of ≤3 μm to obtain glass slurry.
[0031] Step 4: The remaining organic carrier is mixed with glass slurry, silver powder, silver-coated nickel powder, and aluminum alloy powder according to the above amounts, and stirred for 2 hours using a contact planetary mixer until there is no obvious granularity and the fineness is less than 10 μm, thereby obtaining a second mixture; Step 5: Transfer the second mixture to a three-roll mill and roll it to a fineness of ≤3 μm, filter it, and package it. Example 2
[0032] A main grid slurry of high-conductive silver-coated conductive powder, the composition of which is as follows: 20 parts of organic carrier 1.2 parts of inorganic glass powder Silver-coated nickel-coated carbon powder (10% silver, 40% nickel powder, 50% carbon powder) 23.8 parts Silver powder 55 parts Among them, the raw materials of the organic carrier are: PVB 30HH 15 parts 2,2,4-Trimethyl-1,3-pentanediol monoisobutyrate 25 parts 7 parts of 2,2,4-trimethyl-1,3-pentanediol diisobutyrate 40 parts of diethylene glycol butyl ether acetate 5 parts of tributyl citrate 6 parts hydrogenated castor oil 2 parts of oleic acid A method for preparing a main grid slurry of a highly conductive silver-coated conductive powder is as follows: Step 1: PVB 30HH, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, tributyl citrate, hydrogenated castor oil, and oleic acid are prepared according to the above weight ratios, dispersed and dissolved in a high-speed disperser at 80°C, at a speed of 1000 rpm, for 1 hour until clear and transparent, and then cooled to room temperature to obtain an organic carrier.
[0033] Step 2: Take part of the organic carrier and the inorganic glass powder, respectively accounting for 30% and 70%, and mix them to obtain a mixture, stir them in a contact planetary mixer for half an hour, and after no obvious granular feeling, the fineness is measured to be less than 40 μm, to obtain a first mixture; Step 3: Transfer the first mixture to a three-roll mill and roll it to a fineness of ≤3 μm to obtain glass slurry.
[0034] Step 4: The remaining organic carrier is mixed with glass paste, silver powder, and silver-coated nickel-coated carbon powder according to the above amounts, and stirred for 1.5 hours using a contact planetary mixer until there is no obvious granularity and the fineness is less than 10 μm, thereby obtaining a second mixture; Step 5: Transfer the second mixture to a three-roll mill and roll it to a fineness of ≤3 μm, filter it, and package it. Example 3
[0035] A main grid slurry of high-conductive silver-coated conductive powder, the composition of which is as follows: 20 parts of organic carrier 0.6 parts of inorganic glass powder Silver-coated tin-coated copper powder (20% silver, 40% tin powder, 40% copper powder) 54.4 parts Silver powder 25 parts Among them, the raw materials of the organic carrier are: 2 parts acrylic resin 2,2,4-Trimethyl-1,3-pentanediol monoisobutyrate 30 parts 2,2,4-Trimethyl-1,3-pentanediol diisobutyrate 17 parts 40 parts of diethylene glycol butyl ether acetate 5 parts of 2-ethylhexyl palmitate Titanate coupling agent 1 part 2 parts polyamide wax 2 parts of oleic acid A method for preparing a main grid slurry of a highly conductive silver-coated conductive powder is as follows: Step 1: prepare acrylic resin, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, diethylene glycol butyl ether acetate, isooctyl palmitate, titanate coupling agent, polyamide wax, and oleic acid according to the above weight parts, disperse and dissolve them in a high-speed disperser at a temperature of 80°C, a speed of 1000 rpm, and a time of 1 hour until clear and transparent, and then cool to room temperature to obtain an organic carrier;
[0036] Step 2: Take part of the organic carrier and the inorganic glass powder, respectively accounting for 30% and 70%, and mix them to obtain a mixture, stir them in a contact planetary mixer for half an hour, and after no obvious granular feeling, the fineness is measured to be less than 35 μm, to obtain a first mixture; Step 3, transferring the first mixture to a three-roll mill and rolling it to a fineness of ≤3 μm to obtain a glass slurry;
[0037] Step 4: The remaining organic carrier is mixed with glass slurry, silver powder, and silver-coated nickel-coated carbon powder according to the above amounts, and stirred for 1 hour using a contact planetary mixer until there is no obvious granularity and the fineness is less than 10 μm; Step 5: Transfer the second mixture to a three-roll mill and roll it to a fineness of ≤3 μm, filter it, and package it.
[0038] Comparative Example 1 The comparative example provides a high-conductivity main grid silver paste, the composition of which is as follows: 17 parts of organic carrier 1.2 parts of inorganic glass powder Silver powder 81.8 parts Among them, the organic carrier component is: 5 parts of ethyl cellulose 2,2,4-Trimethyl-1,3-pentanediol monoisobutyrate 20 parts 48 parts of diethylene glycol butyl ether acetate Polyamide wax 8 parts TDO 5 parts 2 parts dimethyl silicone oil A method for preparing a high-conductivity main grid silver paste comprises the following steps: Step 1: Prepare ethyl cellulose, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, diethylene glycol butyl ether acetate, polyamide wax, TDO and dimethyl silicone oil in the above proportions, disperse and dissolve them in a high-speed disperser at 80°C, at a speed of 1000 rpm for 1 hour until the mixture becomes clear and transparent, and then cool to room temperature.
[0039] Step 2: Take an organic carrier and an inorganic glass powder and mix them. The two components are prepared in a ratio of 20%:80% to obtain a mixture. Stir it in a contact planetary mixer for half an hour. After there is no obvious granular feeling, the fineness is measured to be less than 15 μm. Step 3, transferring the mixture to a three-roll mill and rolling it to a fineness of ≤3 μm;
[0040] Step 4: The remaining organic carrier, glass paste and silver powder are prepared according to the dosage of the present application, and stirred for 1 hour using a contact planetary mixer until there is no obvious granularity and the fineness is less than 10 μm; Step 5: Transfer the mixture to a three-roll mill and roll it to a fineness of ≤3 μm, filter it, and package it.
[0041] Test example The busbar slurries prepared in Example 1, Example 2, Example 3 and Comparative Example 1 were used on the busbars of photovoltaic solar cells, and their electrical performance was tested: Printing main grid plate parameters: 430 mesh-13 wire diameter-15 yarn thickness-3.5 film thickness-15 opening Printing fine grid screen parameters: 500 mesh-9 wire diameter-13 yarn thickness-3 film thickness-12.5 opening Printing parameters: printing speed 500 mm / s, ink return speed 1000 mm / s Sintering furnace: Maxwell Light injection: Autevi Laser equipment: Deer Tensile testing machine: Ligao horizontal tensile testing machine The performance test results are shown in Table 1.
[0042] Table 1 Electrical performance test data of the main grid used in Examples 1-3 and Comparative Example 1 content Isc [A] Uoc [V] Eta [%] FF [%] Rs TG wet weight pull Example 1 14.0651 0.7258 25.016 80.903 0.00019 11 3.58N Example 2 14.0717 0.7252 25.013 80.920 0.00018 11 4.02N Comparative Example 1 14.0668 0.7259 25.009 80.894 0.00020 11 3.61N Example 3 14.0778 0.7254 25.015 80.899 0.00019 11 3.99N From the electrical performance of the main grids prepared in Examples 1, 2, and 3, the data are within the normal error range and can be determined to be on par with Comparative Example 1. Except for Example 1, which has the same tensile force as Comparative Example 1, the others are higher than Comparative Example 1.
[0043] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, modification, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a main grid slurry of a highly conductive silver-coated conductive powder, characterized in that: The following steps are involved: (1) Mixing part of the organic carrier with inorganic glass powder, wherein the inorganic glass powder accounts for 65-90%, and stirring for 20-40 minutes until there is no obvious granular feeling and the fineness is less than 50 μm, to obtain a first mixture; (2) transferring the first mixture to a three-roll mill and rolling it until the fineness is ≤3 μm to obtain a glass slurry; (3) Mix the remaining organic carrier with the glass slurry, the silver-coated conductive powder and the silver powder, and stir for 1 to 2 hours until there is no obvious granularity and the fineness is less than 10 μm, to obtain a second mixture; (4) The second mixture is transferred to a three-roll mill and rolled until the fineness is ≤ 3 μm to obtain a main grid slurry.
2. The preparation method according to claim 1, characterized in that: The raw materials for preparing the main grid slurry include, by weight: 8-30 parts of organic carrier, 0.5-5 parts of inorganic glass powder, 0.5-65 parts of silver-coated conductive powder, and 0.5-65 parts of silver powder; The particle size of the inorganic glass powder is 0.5-3 μm; The particle size of the silver-coated conductive powder is 0.2-10 μm, and its shape includes one or more of spherical, quasi-spherical, flake, fibrous, and dendritic; The silver powder has a particle size of 0.2-3 μm and a shape of sphere, quasi-sphere, flake, fiber or dendrite; The organic carrier comprises the following components in parts by weight: 1 to 15 parts of resin, 70 to 90 parts of solvent, and 2 to 15 parts of auxiliary agent.
3. The preparation method according to claim 2, characterized in that: The method for preparing the organic carrier comprises the following steps: Weigh each component according to the weight portion in the organic carrier, dissolve the weighed resin and solvent at a temperature of 50-90°C, disperse at a speed of 500-1000 rpm until clear and transparent, cool to room temperature, add an auxiliary agent to mix, and stir for 1-2 hours to obtain an organic carrier.
4. The preparation method according to claim 1, characterized in that: The raw materials for preparing the main grid slurry include, by weight: 20-30 parts of organic carrier; 2.5-4 parts of inorganic glass powder; 35-65 parts of silver-coated conductive powder; Silver powder 0.5-35 parts.
5. The preparation method according to claim 1, characterized in that: The inorganic glass powder is a powder obtained by melting inorganic oxides at a high temperature of 900-1500°C to form a glass body, cooling, grinding or jet milling; The inorganic oxides include lead oxide, titanium oxide, copper oxide, silicon dioxide and boron oxide.
6. The preparation method according to claim 1, characterized in that: The silver-coated conductive powder is one or more of silver-coated copper powder, silver-coated tin powder, silver-coated nickel powder, silver-coated carbon powder, silver-coated tin-coated copper powder, silver-coated carbon-coated copper powder, silver-coated nickel-coated carbon powder, silver-coated tin-coated carbon powder, and alloy powder; The mass percentage of silver in the silver-coated conductive powder is 10-80%.
7. The preparation method according to claim 1, characterized in that: In the organic carrier, the resin is selected from at least one of ethyl cellulose resin, cellulose resin, PVB resin, SEBS resin, SBS resin, acrylic resin, polyester resin, polyurethane resin and phenolic resin; The solvent is selected from at least one of diethylene glycol butyl ether, diethylene glycol hexyl ether, diethylene glycol butyl ether acetate, diethylene glycol dibutyl ether, 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate, 2,2,4-trimethyl-1,3-pentanediol diisobutyrate, tributyl citrate, dibutyl phthalate, isooctyl palmitate, terpineol, and DBE; The additives include one or more of dispersants, leveling agents, coupling agents, and thixotropic agents.
8. The preparation method according to claim 7, characterized in that: The dispersant includes polyurethane modified dispersant, modified polyester dispersant, oleic acid, stearic acid, TDO, acrylic dispersant; The leveling agent includes silicone, acrylic, polysiloxane, and silicone oil; The coupling agent includes a silane coupling agent, a titanate coupling agent, an aluminate coupling agent, and a chromium complex coupling agent; The thixotropic agent includes an inorganic thixotropic agent, hydrogenated castor oil and its derivatives, and polyamide wax.
9. Application of the busbar slurry of highly conductive silver-coated conductive powder prepared by the preparation method according to any one of claims 1 to 8 in the busbar of a photovoltaic solar cell.